Development and application of a diagnostic instrument to evaluate secondary students' conceptions of qualitative analysis - Tan, Kim C.D. (Curtin University, 2000)
The primary purpose of this study was to develop a two-tier multiple choice diagnostic instrument to assess Singapore Grade 10 students' (15 to 17 years old) understanding and alternative conceptions of qualitative analysis. Additional and related purposes were to determine whether more advanced chemistry students, for example, junior college (Grade 11 and 12) students, undergraduates and graduate trainee-teachers have a better understanding of basic qualitative analysis than secondary students, and to develop appropriate teaching strategies and materials on qualitative analysis based on the findings of this study and a review of the literature on practical work.The results from the administration of the diagnostic instrument showed that Singapore Grade 10 students had many alternative conceptions related to qualitative analysis, and these were grouped under the headings of 'Displacement', 'Redox', 'Dissolution', 'Addition of acid' and 'Heating'. The cross-age study showed that the more advanced chemistry students generally had a better understanding of basic qualitative analysis but had similar alternative conceptions as the Grade 10 students. However, the alternative conceptions identified were consistently held by only a small number of students across all contexts examined in the diagnostic instrument, suggesting that a number of students either had more than one conception for a particular concept or no conceptions at all. The results from the trial of the qualitative analysis teaching package indicated that the teaching package was feasible. Teachers involved in the trial found it structured and comprehensive, and the students who experienced the teaching package performed better on the diagnostic instrument than a comparison group.The study recommends that better ways of conducting qualitative analysis practical work are required, and using the teaching package may be a step in this direction. The study also raises questions about the value of teaching qualitative analysis in secondary schools when important reactions involved in qualitative analysis are omitted from the syllabus, and when there is little incentive and time in the school curriculum for learners to understand what they are doing in qualitative analysis.